Nationalism Narrative in History Learning In Islamic Education Foundation (A Case Study of Learning History at SMA Al-Islam 1 Surakarta during the COVID-19 Pandemic) - Ari Prasetio; Leo Agung; Sariyatun Sariyatun (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Islamic Education Foundation in Indonesia has gone through several periods, from the era of the Dutch East Indies government to the present. An Islamic foundation which is quite important in the journey of nationalism in Indonesia is the Al-Islam Higher Education Foundation which was founded in 1928. The purpose of this study is to review the extent to which the SMA Al-Islam 1 Surakarta foundation is full of historical values in carrying historical learning with the narrative of nationalism. The method used is descriptive qualitative with purposive sampling technique on several teachers, staff, and students in the school environment. The results of this study indicate that the narrative of nationalism conveyed in history learning at SMA Al-Islam 1 Surakarta certainly has Islamic learning characteristics, even though it is in a conventional learning context. The teacher's background, which is equipped with scientific and distinctive Islamic studies, further encourages teachers to integrate the saga, arguments, hadiths, and ulama's fatwas into the narrative of nationalism. Interestingly, the history lessons carried out by teachers face challenges because they are faced with pandemic conditions that have hindered learning and forced schools to do online learning (online). This then deepens the studies carried out by researchers regarding the ways that teachers adapt to online learning to convey historical learning containing the narrative of nationalism in the midst of a pandemic.